The influence of X-irradiated to dose 1057 R LiF crystals' tooling on their optical descriptions - Petchenko, G.O.; Boiko, S.M. (Вопросы атомной науки и техники, 2018)
Here there were investigated the influence of plastic deformation ε on the optical characteristics of Х-irradiated
to dose 1057 R LiF crystals and the colorimetric characteristics of optical radiation passing through crystals with
ε. It was established that change of strains in the interval 0.155...3.3% leads to reversible changes in the
spectral dependences of the transmittance coefficient τλ (λ), as well as the coordinates of the color and brightness of
the radiation, passing through the crystal, but the color of the radiation thus remains constant. Досліджено вплив пластичної деформації ε на оптичні характеристики опромінених до дози 1057 Р кристалів LiF і колориметричні характеристики оптичного випромінювання, що проходить через кристали з різними ε. Встановлено, що зміна деформації в інтервалі 0,155…3,3% призводить до оборотних змін спектральних залежностей коефіцієнта пропускання τλ (λ), а також координат кольору і яскравості випромінювання, що проходить через кристал, але колірність випромінювання при цьому залишається на сталому рівні. Исследованы влияния пластической деформации ε на оптические характеристики облученных до дозы
1057 Р кристаллов LiF и колориметрические характеристики оптического излучения, проходящего через
кристаллы с разными ε. Определено, что изменение деформации в интервале 0,155…3,3% приводит к обратимым изменениям спектральных зависимостей коэффициента пропускания τλ (λ), а также координат цвета
и яркости излучения, проходящего через кристалл, но цветность излучения при этом остается на постоянном
уровне.